2004
DOI: 10.1016/j.jfms.2003.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of infectious diseases in feral cats in Northern Florida

Abstract: Objectives of this study were to determine prevalence of infection in feral cats in Northern Florida with a select group of infectious organisms and to determine risk factors for infection. Blood samples or sera from 553 cats were tested with a panel of antibody, antigen or PCR assays. Male cats were at higher risk for FIV, Mycoplasma haemofelis, and M. haemominutum. Infection with either FeLV or FIV was associated with increased risk for coinfection with the other retrovirus, M. haemofelis, or M. haemominutum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
124
7
25

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(179 citation statements)
references
References 65 publications
23
124
7
25
Order By: Relevance
“…Unlike our results, feline hemoplasma infection has reported to be correlated with male gender, non-pedigree status and access to the outdoors (SYKES et al, 2008;WILLI et al, 2006a, b;TASKER et al, 2003;GRINDEM et al, 1990;LURIA et al, 2004). Some studies (NASH;BOBADE, 1986;GRINDEM et al, 1990;HARRUS et al, 2002;MACIEIRA et al, 2008;SYKES et al, 2008;GENTILINI et al, 2009) but not others (WILLI et al, 2006a;DE BORTOLI et al, 2012) have shown an association between retrovirus infection and hemoplasmosis.…”
Section: Discussioncontrasting
confidence: 76%
“…Unlike our results, feline hemoplasma infection has reported to be correlated with male gender, non-pedigree status and access to the outdoors (SYKES et al, 2008;WILLI et al, 2006a, b;TASKER et al, 2003;GRINDEM et al, 1990;LURIA et al, 2004). Some studies (NASH;BOBADE, 1986;GRINDEM et al, 1990;HARRUS et al, 2002;MACIEIRA et al, 2008;SYKES et al, 2008;GENTILINI et al, 2009) but not others (WILLI et al, 2006a;DE BORTOLI et al, 2012) have shown an association between retrovirus infection and hemoplasmosis.…”
Section: Discussioncontrasting
confidence: 76%
“…Sendo assim, o protocolo para reação de PCR, em uma única etapa de reação, avaliado neste trabalho, foi eϐicaz e especíϐico para o diagnóstico de E. canis na espécie felina. Vale ressaltar que a parasitemia nesta espécie é bem menor que em cães, (Luria et al 2004;Lappin et al 2005, Shaw et al 2005, Eberhardt et al 2006) sendo imprescindível estabelecer o limiar de detecção das espécies erliquiais no sangue de felinos pelas técnicas de PCR em etapa única.…”
Section: Methodsunclassified
“…Também é possível que os gatos deste estudo possuam menor número de cópias circulantes de DNA de Ehrlichia spp. que os cães, ou ainda, que a alíquo-ta da amostra coletada não tivesse a presença de mórulas, gerando resultados falso-negativos (Luria et al 2004, Lappin et al 2005, Eberhardt et al 2006). Segundo Shaw et al (2005), felinos parecem ser menos predispostos que cães a certas doenças transmitidas por carrapatos, tais como erliquiose, babesiose e hepatozoonose e também questiona a possibilidade dos felinos apresentarem uma resistência inata ou adaptativa à infecção que limita o desenvolvimento da doença ou de certa forma, comprometem a transmissão de agentes pelos carrapatos.…”
Section: Methodsunclassified
“…Feral cats 6,7 or endangered wild felids as linx and panthers 8 are also under risk of FeLV infection. Both retroviruses affect the immune system and are causes of significant morbidity and mortality 9 or predispose to infections such as hemotropic mycoplasmas 10 or feline infectious peritonitis 11 .…”
Section: Introductionmentioning
confidence: 99%